Problem Decomposition Skills, Mathematical Maturity, and Their Relation to Mathematics Problem-Solving in A Computer Science Learning Class - Prabawa, Harsa Wara; Rosjanuardi, Rizky; Nurlaelah, Elah (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2023)
This study investigates how students represent ideas when decomposing mathematical problems and how their mathematical maturity influences the problem-solving process. The method used in this research is explorative research. The subject of this research was six Computers Science Education Department students at the Indonesian Education University. The instrument used task-based interviews. Data analysis used the concept of Miles and Huberman, including data reduction, presentation, and drawing conclusions. The research found that problem decomposition skills, mathematical maturity, and their relation to solving mathematical problems in computer science learning classes influenced one another. Decomposition skills were influenced by how basic math skills are taught, so they can affect students' maturity in solving math problems.